Outcome of Urethroplasty in Management of Urethral Stricture: Experience at Institute of Kidney Diseases Hayatabad Peshawar - Majid Khan Kakakhel, Arshad, Tanveer Ahmad, Aamir Khan, Muhammad Jafar, Abdullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of successful outcomes of urethroplasty in the management of urethral stricture Methods: It is a descriptive study, conducted in the department of Urology at the Institute of Kidney diseases Peshawar from April 2016 to December 2019. A total number of 85 patients for urethroplasty were included in the study by non-probability convenient sampling. The entire pre-operative, per-operative, and postoperative data were collected on structured proforma and analyzed on SPSS®, version 20.0. Results: The mean age of the patient in this study was 41 years. Regarding etiology, External trauma was the major cause in the form of road traffic accidents in 38.82% while straddle urethral injury in 29.41% of patients, other less frequent causes included iatrogenic urethral trauma and infective stricture. The bulbar urethral stricture was found in 55.29% of cases, with proximal penile and bulboperineal accounting for 23.52% and 21.17% respectively. Significant past surgical history found was suprapubic catheterization in 100%, a failed primary attempt of internal optical urethrotomy (IOU) in 29.41%, multiple recurrences in 48.23%, and re-do urethroplasty in 10.58% of cases. The most common procedure performed was end-to-end anastomotic urethroplasty in 81%, other procedures included penile flap urethroplasty, pull-through procedure, and 10.58% of cases required pubectomy. Urethroplasty was found highly successful in 94% of mean follow-ups 15 months. The cause of failure was wound infection in 1, UTI in 2, and necrosis of penile skin flap in 2 patients. Conclusion: Our initial results conclude that anastomotic urethroplasty is an effective and mainstay treatment modality in the management of urethral stricture disease. It bears less rate of recurrence of urethral stricture. Keywords: Urethroplasty, urethro stricture, Recurrence